Avalanche susceptibility mapping with the use of frequency ratio, fuzzy and classical analytical hierarchy process for Uzungol area, Turkey - Varol, Nehir (Cold regions science and technology, 2022)
As expressed in many studies in literature, the dynamic nature of snow avalanches is affected by the meteorological, environmental, topographical and human-related factors of the region. To better appreciate and forecast the snow avalanche, one of the hydro-geological disasters, becomes possible thanks to the approaches that take these parameters into consideration. They are commonly seen in mountainous areas, cause loss of life and property when they reach settlements, energy transmission lines, highways, ski resorts and other structures. Field studies, GIS, remote sensing, and various numerical avalanche modeling programs are used in determining avalanche-prone zones. There are various methods for producing avalanche susceptibility maps. In this study, susceptibility maps were created using the Frequency Ratio (Fr), Analytical Hierarchy Process (AHP), and Fuzzy-AHP (FAHP) methods for avalanche potential, in the tourism region of Uzungol, Trabzon located in northeastern Turkey. There has been no literature so far in the application of Fuzzy-AHP methods on avalanche susceptibility analysis, which has been used in other fields. This work will be the first case study on this subject. The results were compared according to existing land and inventory data; the success rates of the methods were found to be 89.12% for Fr, 71.15% for AHP and 73.24% for FAHP, and the effectiveness of the Fuzzy-AHP method was further tested. Comparing the results of the different methods, it has been found out that the Fr method is the most successful, while the AHP and FAHP methods provide approximate results. •Avalanche susceptibility mapping•Frequence Ratio•Classical AHP•Fuzzy AHP•Avalanche risk management•GIS